Is gardening corals of opportunity the appropriate response to reverse Philippine reef decline? - Feliciano, Giannina Nicole R. (Animo Repository, 2018)
Hard coral cover (HCC) in the Philippines has been declining over the past decades. Restoration practices that utilize “gardening” corals of opportunity (COPs) are actively being adopted throughout the country. However, the use of COPs in coral gardening has not yet been examined in terms of its effectiveness in addressing nationwide-scale reef decline. The feasibility of using COPs for coral gardening was determined through a spreadsheet model that derives COP numbers needed to increase HCC in a reef. The model showed that 280,112 COPs of 5-cm radius need to be transplanted to increase HCC in a hectare of reef from 0% to 22%, the current national average. Annual COP mortality must be less than 31.5% to achieve an increase in HCC above 22% over a span of 10 years following a gardening effort. Actual counts and generic composition of available COPs were recorded from transects in 20 reef stations across three locations in the Philippines (Lian, Luzon; Lubang Island; and Balabac, Palawan). Natural COP densities suggest that large areas of healthy reefs must be searched to obtain enough COPs for an effective gardening effort. Furthermore, the COPs measured in Lian were below the recommended fragment size for transplantation, thus needing nursery rearing to attain the 5-cm radius prescribed for increased probability of transplant survivorship. These findings indicate that applying coral gardening at a nationwide scale is not likely to be feasible, effective, or sustainable.